(untitled) (Acta Scientiarum. Technology, 2021)
Endophytes may play important roles in agriculture. Spontaneous or induced mutant strains may increase their biotechnological properties. Seventeen Colletotrichum endophytic fungi were investigated for their plant growth-promoting characteristics (in vitro phosphate solubilization, IAA, and siderophore production). The five best strains were inoculated into bean seeds, and the most prominent isolate was selected to obtain auxotrophic mutants by Potassium Bromate Resistance System (PBRS). The plant growth-promoting ability of the mutant was also investigated. Further, 41.17% of the evaluated endophytes presented promising results for in vitro assays (C. karstii SL10, C. karstii SL28, C. karstii SL57, C. karstii SL59, C. karstii SL12, C. karstii SL40, and C. karstii SL24). The endophyte C. karstii SL57 was statistically conspicuous for plant height and root length when compared to those in control plants. Bromate-resistant mutant C. karstii SL57 increased in vitro phosphate solubilization (23%) and chlorophyll levels (Chlb 0.607 mg g-1 and Chlt 0.973 mg g-1) of bean plants when compared to the wild-type strain (Chlb 0.551 mg g-1 and Chlt 0.881 mg g-1). This is the first time an auxotrophic mutant fungus has been obtained by PBRS with a biotechnological application for the agricultural field